Anti-Corruption Policies and Programs : A Framework for Evaluation - Huther, Jeff; Shah, Anwar (World Bank, Washington, DC, 2014)
The anti-corruption strategy the World Bank announced in September 1997 defined corruption as the "use of public office for private gain" and called for the Bank to address corruption along four dimensions: 1) Preventing fraud and corruption in Bank projects; 2) Helping countries that request Bank assistance for fighting corruption; 3) Mainstreaming a concern about corruption in Bank work; and 4) Lending active support to international efforts to address corruption. The menu of possible actions to contain corruption (in both countries and Bank projects) is very large, so the authors develop a framework to help assign priorities, depending on views of what does and does not work in specific countries. Their framework, based on public officials' incentives for opportunistic behavior, distinguishes between highly corrupt and largely corruption-free societies. Certain conditions encourage public officials to seek or accept corruption: a) The expected gains from undertaking a corrupt act exceed the expected costs. b) Little weight is placed on the cost that corruption imposes on others. In a country with heavy corruption and poor governance, the priorities in anti-corruption efforts would then be to establish rule of law, strengthen institutions of participation and accountability, and limit government interventions to focus on core mandates. In a country with moderate corruption and fair governance, the priorities would be decentralization and economic reform, results-oriented management and evaluation, and the introduction of incentives for competitive delivery of public services. In a country with little corruption and strong governance, the priorities might be explicit anti-corruption agencies and programs, stronger financial management, increased public and government awareness, no-bribery pledges, efforts to fry the "big fish," and so on.